(untitled) (CAHIERS MAGELLANES-NS, 2024)
This paper investigates the environmental sustainability practices in corporate supply chains through case studies from diverse global industries. It explores the significance of sustainable supply chain management in enhancing business operations' environmental and social impacts, driven by stakeholder pressures. Using a multiple case study design, the research examines the sustainability efforts of various industries, including FMCG, automotive, oil and mining, forestry, chemicals, pharmaceuticals, and information technology, across major Indian cities: Mumbai, Delhi, Bangalore, Chennai, and Hyderabad. Data were collected from secondary sources such as sustainability reports, company websites, and industrial publications, supplemented by telephonic interviews with sustainability managers. The findings reveal significant variations in sustainability practices across industries and regions. FMCG and Information Technology sectors demonstrate high commitment through robust governance structures, capacity building, and innovative initiatives, driven by consumer engagement and regulatory compliance. Conversely, the Oil and Mining sector shows lower engagement in sustainability practices, prioritizing financial performance over environmental and social responsibilities. The analysis highlights the influence of competitive forces, regulatory environments, and consumer expectations on sustainability practices. The study underscores the need for industries to adopt comprehensive and collaborative sustainability strategies, integrating ethical supply chain practices, emissions reduction, and community development. This holistic approach is essential for achieving sustainable corporate performance and meeting future generations' needs. The research contributes to understanding the current trends and challenges in corporate sustainability and provides insights into best practices for enhancing environmental standards in global supply chains.